The Theme of the Five Biscuits: Murphy, Foucault, and Beckett’s Critique of Neoliberalism - Dominic Walker (Estudios Irlandeses, 2019)
Beckett’s Murphy grew out of “Lightning Calculation”, a short story about biscuits and the tragic incommutability of preference. Beckett likely borrowed this rare Americanism from Thorstein Veblen, who uses it to describe the “neo-classical” economic subject, a “hedonistic … lightning calculator of pleasures and pains”. This essay argues that Murphy’s predicament is consistent with Veblen’s “neo-classical” subject and, a fortiori, Foucault’s neoliberal subject in The Birth of Biopolitics. Using Freud’s “Theme of the Three Caskets”, the essay suggests that, while death might no longer be the prerogative of “sovereign power”, it is still felt as the duress of “utility maximisation” with the ultimate “budget constraint” of the human lifespan.